PENGARUH PEMBERIAN PUPUK ORGANIK CAIR DENGAN NPK TERHADAP PERTUMBUHAN BIBIT KAKAO (Theobroma cacao L.) - Nawaridah '; Murniati '; Sukemi Indra Saputra (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This research aimed to know the effect of liquid organic fertilizer made ​​from tofu with NPK and to get the best dose for the growth of cocoa seedlings. This research was carried out experiments with liquid organic fertilizer combination treatment with NPK arranged according to completely randomized design ( CRD ) which consists of 6 levels : P1 = liquid organic fertilizer 200 ml +NPK 7,5 g/polybag, P2 = liquid organic fertilizer 400 ml +NPK 7,5 g/polybag, P3 = liquid organic Fertilizer 600 ml + NPK 7,5 g/polybag, P4 = liquid organic fertilizer 200 ml + NPK 15 g/polybag, P5 = liquid organic fertilizer 400 ml + NPK 15 g/polybag and P6 = liquid organic fertilizer 600 ml + NPK 15 g/polybag. Each treatment was repeated four times so that there are 24 experimental units. Parameters measured were seedling height (cm), number of leaves (strands), leaf area (cm2), stem diameter (cm), the ratio of the root crown and seedling dry weight (g). The data analysis results were significant statistical test followed by Duncun test at 5 % level. Giving a combination of liquid organic fertilizer with NPK significant effect on all parameters observed that seedling height, number of leaves, leaf area, stem diameter, crown ratio of dry weight of roots and seeds of cocoa and a combination of liquid organic fertilizer NPK 200 ml with 7,5 g/polybag produces the best cocoa seedling growth . Keywords : cocoa , liquid organic fertilizer , NPK